2009
DOI: 10.1186/1744-8069-5-44
|View full text |Cite
|
Sign up to set email alerts
|

The Endogenous Hydrogen Sulfide Producing Enzyme Cystathionine-β Synthase Contributes to Visceral Hypersensitivity in a Rat Model of Irritable Bowel Syndrome

Abstract: BackgroundThe pathogenesis of visceral hypersensitivity, a characteristic pathophysiological feature of irritable bowel syndrome (IBS), remains elusive. Recent studies suggest a role for hydrogen sulfide (H2S) in pain signaling but this has not been well studied in visceral models of hyperalgesia. We therefore determined the role for the endogenous H2S producing enzyme cystathionine-β-synthetase (CBS) in a validated rat model of IBS-like chronic visceral hyperalgesia (CVH). CVH was induced by colonic injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
84
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 39 publications
11
84
0
Order By: Relevance
“…STZ has been widely used to induce type 1 diabetes in rodents for the study of diabetic neuropathic pain (Grabauskas et al, 2011;Xu et al, 2011). In the present study, after a single intraperitoneal injection of STZ (65 mg/kg body weight), we monitored rat blood glucose level and body weight once every week for 5 weeks.…”
Section: Stz Injection Induces Gastric Hypersensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…STZ has been widely used to induce type 1 diabetes in rodents for the study of diabetic neuropathic pain (Grabauskas et al, 2011;Xu et al, 2011). In the present study, after a single intraperitoneal injection of STZ (65 mg/kg body weight), we monitored rat blood glucose level and body weight once every week for 5 weeks.…”
Section: Stz Injection Induces Gastric Hypersensitivitymentioning
confidence: 99%
“…We have recently reported that the endogenous H 2 S-producing enzyme cystathionine-␤-synthetase (CBS) played an important role in chronic visceral hypersensitivity (Xu et al, 2008;Xu et al, 2009;Li et al, 2012; and that peripheral inflammation led to cbs gene DNA demethylation (Qi et al, 2013), indicating a crucial role for CBS and an epigenetic mechanism in chronic pain Qi et al, 2013). However, roles for NF-B and CBS/H 2 S signaling in diabetic gastric hypersensitivity remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…As described previously, 20,22 DRG neurons innervating the colon were labeled by injection of fluorescent dye DiI (Invitrogen, New York, NY, USA) into the colon wall. Rats were anesthetized with chloral hydrate (0.36 g/kg i.p.…”
Section: Cell Retrograde Labelingmentioning
confidence: 99%
“…However, whether H 2 S acts on CSLV afferents is unknown; if it does, then the H 2 S-induced effect and its underlying mechanism remain to be explored. The application of NaHS has been reported to induce somatic hyperalgesia and the depolarization of dorsal root ganglion neurons, which are dependent on transient receptor potential ankyrin 1 (TRPA1) receptors (2,28,48). The TRPA1 receptor, a Ca 2ϩ -permeable, nonselective cation channel, is predominantly expressed on nociceptive sensory neurons that include CSLV neurons (31,40).…”
mentioning
confidence: 99%
“…The application of sodium hydrosulfide (NaHS, a donor of H 2 S) has been demonstrated to induce the sensitization of colon nociceptive neurons (44,48), a counterpart of CSLV neurons in visceral tissues. Moreover, one study showed that the intratracheal instillation of NaHS triggered airway neurogenic inflammation that was nearly abolished by the desensitization of CSLV afferents (41), which implied the effects of H 2 S on the afferents.…”
mentioning
confidence: 99%